Enhancement of in vitro effects of polymeric nanoparticle encapsulated tamoxifin compared to tamoxifen in MCF-7 breast cancer cell line - Tung, En En (2012)
Tamoxifen (TMX) is one of the common hormone therapies for breast cancer treatments. It acts as an anti-estrogen on breast cancer tissues by inducing apoptosis which is regulated by a variety of cellular signalling pathways such as tumour suppressor protein p53 and caspase-9. However, it is associated with side effects at high doses. This suggests the use of nanoparticles (NP) to deliver a lower dose of TMX with an enhance efficiency. Thus, the objective of this research was to assess and compare the in vitro effects of synthesized polymeric NP-encapsulated TMX to TMX toward MCF-7 breast cancer cell line. NP composed mainly of N-isopropylacrylamide (NIPAAm) were synthesized and loaded with TMX. Photon Cross Correlation Spectroscopy Nanophox (PCCS-Nanophox), Transmission Electron Microscopy (TEM), and Fourier Transform Infrared Spectroscopy (FTIR) were used to determine the size, morphology and infrared spectrum of the NP, respectively. The drug release pattern of the NP was investigated through dialysis. To study the cytotoxicity properties, MTT assay was performed on breast cancer cell line, MCF-7. The apoptotic effects were determined qualitatively through acradine orange and propidium iodide (AO/PI) stains with fluorescent microscopy, and quantitatively through FITC Annexin V and PI staining with flow cytometry. The expression levels of tumour suppressor protein p53 and caspase-9 were determined through ELISA. Finally, the data collected were analyzed by One Way Analysis of Variance (ANOVA), Tukey’s test. In this study, the polymeric NP were successfully prepared by gamma irradiation, forming spherical NP at a size of 49.89 ± 0.55 nm in diameter. TEM images showed that the particles were spherical in shape with a distinct core-shell structure. It was demonstrated that the void polymeric NP were non-toxic, and were able to release the drug in a sustained manner with 50.99 ± 1.21 % entrapment efficiency, underscoring the potential of these NP as a carrier for drugs. The proliferation of MCF-7 cells was significantly inhibited by the TMX-NP with a lower 50% inhibitory concentration (IC50) value of 24.63 ± 1.56 μM at 48 hr. It also possessed a greater apoptotic effect, resulting in a percentage of 68.53 ± 3.81% at 32.0 μM. Furthermore, higher levels of p53 (23.22 ± 2.79 U/ml) and caspase-9 (85.35 ± 11.11ng/ml) were detected in a dose-dependent manner. In conclusion, the therapeutic effects of the synthesized TMX NP were enhanced when compared to TMX. Its potential is not limited to anti-cancer drugs, but may also be applied in other drugs and diseases.